Electrochemical studies of copper-aluminum-silver alloys in 0.5 M H2SO4 - Rosatto, S. S.; Cabot, P. L.; Sumodjo, PTA; Benedetti, Assis Vicente [UNESP] (Elsevier B.V., 2001)
The electrochemical behavior in 0.5 M H2SO4 at 25 degreesC of a Cu-Al(9.3 wt%)-Ag(4.7 wt%) alloy submitted to different heat treatments and an annealed Cu- Al(9.7 wt%)-Ag(34.2 wt%) were studied by means of open circuit potential (E-mix) measurements, potentiodynamic polarizations and cyclic voltammetry. SEM and EDX microanalysis were used to examine the changes caused by the electrochemical perturbations. The steady state potentials observed for the studied samples were correlated in terms of the phases present in the alloys surface. The resulting E/I potentiodynamic profiles were explained in terms of the potentiodynamic behavior of pure copper and pure silver. The presence of aluminum decreased the extent of copper oxidation. In the apparent Tafel potential region, two anodic Tafel slopes were obtained: 40 mV dec(-1) in the low potential region and 130 mV dec(-1) in the high potential region, which were related with the electrochemical processes involving copper oxidation. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: copper alloys; aluminum alloys; silver alloys; corrosion